2002
DOI: 10.1542/peds.110.5.884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplemental Oxygen on Sleep Architecture and Cardiorespiratory Events in Preterm Infants

Abstract: Asymptomatic preterm infants exhibit frequent and potentially clinically adverse cardiorespiratory events when assessed in the sleep laboratory. Administration of SupOx to these infants is associated with an increase in the overall duration and percentage TST spent in quiet sleep with reciprocal changes in active sleep. In addition, improvement in respiratory stability is observed with the use of low-flow SupOx, as evidenced by a decrease in apnea, periodic breathing, and bradycardia, without adverse effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 31 publications
(27 reference statements)
2
39
2
Order By: Relevance
“…estimated sleep time without movement or artifactual/uninterpretable periods, CEST) was calculated. A minimum of 4 h of CEST was required (16,17). For infants, it has been shown that reliability of apnea estimation is adequate when recording duration exceeds 3 hours (16 -18).…”
Section: Subjectsmentioning
confidence: 99%
“…estimated sleep time without movement or artifactual/uninterpretable periods, CEST) was calculated. A minimum of 4 h of CEST was required (16,17). For infants, it has been shown that reliability of apnea estimation is adequate when recording duration exceeds 3 hours (16 -18).…”
Section: Subjectsmentioning
confidence: 99%
“…This finding contradicts the substantial body of observational evidence suggesting that higher oxygen targeting can improve growth [30], ameliorate sleep pattern abnormalities [31] and reduce desaturation episodes [32].…”
Section: Tinmentioning
confidence: 61%
“…These authors concluded that oxygen therapy may be a temporary palliative treatment for sleep apnea. Data from previously premature children studied at 38 weeks postconceptional age have also shown improvement in respiratory stability and sleep duration with low-flow oxygen therapy, without compromising alveolar ventilation [43].…”
Section: Oxygen Therapymentioning
confidence: 92%